High Throughput Petrochronology and Sedimentary Provenance Analysis by Automated Phase Mapping and LAICPMS. (21st November 2017) - Vermeesch, Pieter; Rittner, Martin; Petrou, Ethan; Omma, Jenny; Mattinson, Chris; Garzanti, Eduardo
Abstract: The first step in most geochronological studies is to extract dateable minerals from the host rock, which is time consuming, removes textural context, and increases the chance for sample cross contamination. We here present a new method to rapidly perform in situ analyses by coupling a fast scanning electron microscope (SEM) with Energy Dispersive X‐ray Spectrometer (EDS) to a Laser Ablation Inductively Coupled Plasma Mass Spectrometer (LAICPMS) instrument. Given a polished hand specimen, a petrographic thin section, or a grain mount, Automated Phase Mapping (APM) by SEM/EDS produces chemical and mineralogical maps from which the X‐Y coordinates of the datable minerals are extracted. These coordinates are subsequently passed on to the laser ablation system for isotopic analysis. We apply the APM + LAICPMS method to three igneous, metamorphic, and sedimentary case studies. In the first case study, a polished slab of granite from Guernsey was scanned for zircon, producing a 609 ± 8 Ma weighted mean age. The second case study investigates a paragneiss from an ultra high pressure terrane in the north Qaidam terrane (Qinghai, China). One hundred seven small (25 µm) metamorphic zircons were analyzed by LAICPMS to confirm a 419 ± 4 Ma age of peak metamorphism. The third and final case study uses APM + LAICPMS to generate a large provenance data set and trace the provenance of 25 modern sediments from Angola, documenting longshore drift of Orange River sediments over a distance of 1, 500 km. These examples demonstrate that APM + LAICPMS is an efficient and cost effective way to improve the quantity and quality of geochronological data. Plain Language Summary: Much progress has been made in improving the accuracy and precision of geochronological data. However, many Earth Science applications do not so much require better, but simply more data. We have developed a new analytical workflow that is more than twice as efficient than the current state of the art. This new workflow combines a fast scanning electron microscope with a mass spectrometer to simultaneously characterise the chemical, mineralogical and isotopic composition of rocks and minerals. We have applied the new instrument suite to three distinct geological settings to generate high quality data in a fraction of the time that it would have taken conventional studies of the same size and scope. Key Points: We combine automatic phase mapping (APM) by SEM/EDS with laser ablation mass spectrometry (LAICPMS) The new workflow produces paired mineralogical and isotopic data sets for hand specimens and thin sections APM + LAICPMS increases throughput of igneous, metamorphic, and sedimentary studies